HISTORICAL GEOGRAPHY OF THE FOOD INDUSTRY OF NAVOI REGION IN THE YEARS OF INDEPENDENCE (World Bulletin of Social Sciences, 2025)
This article analyzes the historical development of the food industry of Navoi region in the period after Uzbekistan gained independence from a geographical perspective. The article examines the main stages, such as the industrial heritage of the Soviet era, changes during the transition to a market economy, the growth of investments, the establishment of new enterprises and the modernization of existing ones. It also studies the dynamics of the territorial location of production enterprises in various sectors of the food industry (sugar, wine, fruit and vegetable processing, milk, oil, meat, fish, bread and confectionery), the influence of raw materials sources and consumer markets. The article also analyzes the role of small businesses in the industry and future development trends